Extinction and renewal of cue-elicited reward-seeking. (December 2016) - Bezzina, Louise; Lee, Jessica C.; Lovibond, Peter F.; Colagiuri, Ben
Abstract: Reward cues can contribute to overconsumption of food and drugs and can relapse. The failure of exposure therapies to reduce overconsumption and relapse is generally attributed to the context-specificity of extinction. However, no previous study has examined whether cue-elicited reward-seeking (as opposed to cue-reactivity) is sensitive to context renewal. We tested this possibility in 160 healthy volunteers using a Pavlovian-instrumental transfer (PIT) design involving voluntary responding for a high value natural reward (chocolate). One reward cue underwent Pavlovian extinction in the same (Group AAA) or different context (Group ABA) to all other phases. This cue was compared with a second non-extinguished reward cue and an unpaired control cue. There was a significant overall PIT effect with both reward cues eliciting reward-seeking on test relative to the unpaired cue. Pavlovian extinction substantially reduced this effect, with the extinguished reward cue eliciting less reward-seeking than the non-extinguished reward cue. Most interestingly, extinction of cue-elicited reward-seeking was sensitive to renewal, with extinction less effective for reducing PIT when conducted in a different context. These findings have important implications for extinction-based interventions for reducing maladaptive reward-seeking in practice. Highlights: Reward cues can elicit reward-seeking via Pavlovian-instrumental transfer. Extinction reduces the ability of the reward cue to elicit reward-seeking. Reward-seeking following extinction renews when tested in a different context.